The Influence of Investment and Funding Decisions on Company Value with Intervening Variables of Dividend Policy in Companies Listed on The Jakarta Islamic Index - Farakhan Zaki, Putra; Widiyanti, Marlina; Thamrin, Kms. M Husni; Yuliani, Yuliani; Andriana, Isni (Pusat Publikasi Nusantara, 2023)
The purpose of this study is to analyze and apply the influence of investment decisions and funding decisions on company value in companies listed in the Jakarta Islamic Index and to analyze and apply the influence of investment decisions and funding decisions on company value with intervening variables of dividend decisions in companies listed in the Jakarta Islamic Index. The population in this study is companies listed in the Jakarta Islamic Index (JII) for the 2017-2022 period. Research samples with porpusive sampling method amounted to 7 from 30 companies. The data was analyzed using linear regression with the Eviews application. The results showed that Investment decisions and funding decisions have a positive and significant influence on Dividend Policy, Investment Decisions and Funding decisions have no and insignificant effect on company value, dividend policy Intervening investment decisions and funding decisions on company value in companies listed in JII for the 2017-2022 period